Metode Onion Skin: Transformasi Konseptual Siswa dalam Menyelesaikan Persamaan Aljabar Berbasis Deep Learning - Ainurrohmah, Devi Ayu; El Walida, Sikky (JRPM (Jurnal Review Pembelajaran Matematika), 2026)
Mathematics learning in secondary education requires strengthening students' conceptual understanding and quality of thinking processes. However, students' learning practices still tend to be procedural and non-visual, so that the solutions used by students are often less adaptive and meaningless. This study aims to describe students' strategic orientation toward using the Onion Skin Method (draw the skin, peel the skin, and simplify the solution) in solving simple linear equation systems based on algebraic concepts through a Deep Learning approach. The research method used is qualitative descriptive. Sampling involved 10th-grade students at MAN 2 Lamongan in the 2025/2026 academic year, who were selected using purposive sampling with 3 students taken from each level (high, medium, and low). Data were collected through observation, test result analysis, and reflection to explore the reasons for choosing the method. The results showed that students' solution method orientation developed gradually. As the material became more difficult, students consciously began to integrate the Onion Skin Method as an advanced method for problem solving. This method was chosen because it helped students organize the steps of the solution systematically, neatly, and meaningfully, thereby minimizing procedural errors in complex problems. The steps of the Onion Skin Method make students feel visually mindful and joyful, so that the application of the Deep Learning Approach plays an important role in fostering metacognitive awareness. Finally, it can be concluded that the Onion Skin Method with the Deep Learning approach is a tool that is integrated with a deep understanding of algebraic concepts in solving simple linear equations.